Formulation and evaluation of amlodipine and metoprolol bilayer tablets - Lavanya Sreepada; GS Sharma (International Journal of Pharmacy and Analytical Research, 2022)
Background The objective of the present research, an attempt has been made to formulate bi-layered tablets of Amlodipine besylate and Metoprolol succinate. The main objective for combination therapy is to encourage the use of lower doses of drug to reduce the patient’s blood pressure, to minimize dose dependent side effects and adverse reactions. Materials and Methods Various formulations of extended release part of Metoprolol succinate were developed using various polymers like HPMC K15M, HPMC K100M in different proportion and combinations by direct compression technique, Bulk density, tapped density, compressibility index, and hausner’s ratio before being punched as tablets. Results All the evaluated parameters of the optimized formulation optimized formula showed the metoprolol succinate drug release over a period of 16 to 20 hours. and the amlodipine besylate (IR) release the max drug in 60 minutes showed compliance with pharmacopoeial standards. Results of in vitro release profile indicated that formulation 9FDT-IV was the most promising formulation as the extent of drug release from this formulation was optimum (IHS) when compared to other formulations. It was observed that tablets of batch 9FDT-IV followed the Zero order release profiles. Conclusion From the above results and discussion it was concluded that formulation of Extended release tablet of Metoprolol succinate containing 19.5% of HPMC K 15 M, batch 9FDT-IV can be taken as an ideal or optimized formulation of Extended release tablets for 20-hour release as it fulfils all the requirements for Extended release tablet.